Tinjauan Hukum Islam dan Kuhp terhadap Perbuatan Zina - Bintang Okta Ramadhani; Intan Rosari Andini; Nazwa Felinda; Ricy Hilmayandani; Sephia Wulandari; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Adultery, which in Islam is defined as sexual intercourse outside of a legal marriage, is one of the major sins. Islamic law strictly prohibits and imposes severe sanctions on perpetrators of adultery, both men and women. In the Qur'an, adultery is referred to as an act that damages morals and social order. Sanctions for perpetrators of adultery in Islamic law are included in the category of hudud punishments, which have fixed provisions from Allah and are strictly regulated in the Shari'a. The purpose of this study is to analyze how Islamic law imposes sanctions on adultery and the role of these punishments in maintaining the morality of society, to examine how the Criminal Code in Indonesia regulates adultery, and to consider the differences in sanctions applied in positive law, to compare the perspectives of Islamic law and the Criminal Code in dealing with cases of adultery, both in terms of legal substance and enforcement in Indonesia, to identify the relevance of each legal system in dealing with adultery in the modern era, considering the differences in culture and views of society. In Islamic law, adultery has very severe sanctions. If the perpetrator of adultery is a married person, the punishment is stoning or stoning to death, while for those who are not married, the punishment is 100 lashes. This research method uses a qualitative approach with a normative juridical method to analyze the comparison between Islamic law and the Criminal Code in regulating adultery. The results of this study indicate that Islamic law emphasizes the importance of testimony and strong evidence in the process of enforcing the punishment for adultery, namely that there must be four witnesses who directly witnessed the act. Meanwhile, in the Criminal Code, adultery is not given the same severe sanctions as in Islamic law. The Criminal Code only provides imprisonment for adultery perpetrators who are proven guilty, especially if the act involves married parties. Article 284 of the Criminal Code regulates a maximum prison sentence of nine months for those who commit adultery. Unlike Islamic law, the Criminal Code focuses more on maintaining public order and family honor than on individual morality according to religion.